A Rare Cause of Reactive Arthritis: Giardia Lamblia - Dilek Karakuş; Nilüfer Kutay Ordu Gökkaya; Fügen Oktay; Halil Uçan (Archives of Rheumatology, 2009)
Although many of parasitic infestations are known to cause arthritis development, articular findings related to parasitosis is rarely discussed in literature. The protozoa, Giardia lamblia is often known as gastroenteritis agent, on the other hand rarely causes reactive arthritis. The clinical presentation related to articulation are arthritis and arthralgia. In our report, a case with reactive arthritis due to Giardia lamblia is presented with emphasis on the differences in diagnosis and treatment. (Turk J Rheumatol 2009; 24: 51-2)